Identificación con Modelos Discretos para Sistemas Lineales. Modelo Matemático y Aplicaciones - Soriano Méndez, José Jairo; Escobar Díaz, Andrés; Peña Ospina, Rodrigo (Ingeniería, 2002)
This document develops a technical of identification of systems based on lineal models. This is a very powerful alternative to identify any type of real process. Here works on the analysis of discrete processing and in the area of system identification. The article begins with the study of the lineal discrete models that they are used to represent real processes. An algorithm of identification of parameters is used for these models based on the method of least squares. After a methodology is defined to prove test the identification algorithm, which makes analysis of data and implementation with Matlab and LabView, also precise the processes that are manipulated for identification etc. Lastly a mathematical base is given to evaluate the identification system, showing results of the made experiments and applications for the identification system in control.